Retrieval Analysis of Posterior Stabilized Polyethylene Tibial Inserts and Its Clinical Relevance - Pang, Hee-Nee; Jamieson, Paul; Teeter, Matthew G.; McCalden, Richard W.; Naudie, Douglas D.R.; MacDonald, Steven J. (The Journal of arthroplasty, 2014)
This was a retrieval analysis of 83 PS inserts to assess the effect of limb alignment, implant position and joint line position on the pattern of wear in posterior stabilized (PS) tibial inserts. The total damage score was significantly higher in knees with postoperative varus alignment more than 3° (P = 0.03). The total damage score to the post was significantly more in knees with joint line elevation more than 5 mm (9.7 ± 3.9, compared to 6.5 ± 3.7 in knees with less joint line elevation) (P = 0.05). Limb malalignment and joint line elevation resulted in more damage in PS inserts. An external rotation subluxation damage pattern was found in joint line elevation.